Pengaruh Daya Tarik Audiovisual Influencer terhadap Kerterlibatan Perilaku Konsumen dengan Interaksi Influencer-Pelanggan sebagai Mediasi - Reswara, Hening Hasna; Winarno, Wing Wahyu; Biyanto , Frasto (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to determine the influence of influencers' audiovisual attractiveness on consumer behavioral engagement, with influencer-customer interaction as a mediating factor. The study employs the Source Credibility Theory, focusing on the dimensions of attractiveness, expertise, and trustworthiness. Influencers, through video content sharing their personal experiences and recommendations, can evoke positive responses from consumers. This research also explores how audiovisual content and influencer marketing on TikTok, a rapidly growing platform in Indonesia, affect consumer engagement with online booking platforms for hotels and transportation. The study was conducted using a survey method, distributing questionnaires via Google Forms, and analyzed using SEM Smart PLS 3.0. The study aims to fill the gap in understanding the role of audiovisual attractiveness in fostering consumer engagement within the context of online booking services in Indonesia. The findings are expected to guide marketing strategies and provide insights for future research in consumer behavior and influencer marketing.